Inquiry and Research Skills for Language Teachers - Dikilitaş, Kenan; Bostancıoğlu, Ali (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book equips pre-service language teachers with research and inquiry skills which they can use in the course of their classroom teaching. Research is presented not as an additional burden in teachers' busy lives but as an integrated tool for satisfying their curiosity, developing an investigative stance, and strengthening the links between theory and practice. Over the course of the book, the authors introduce and encourage the use of pedagogically exploitable pedagogic-research activities (PEPRAs) to develop a deeper understanding of pedagogic issues in an engaging, supportive, and collaborative way. This book will be of interest to students and instructors on TESOL and related courses, as well as practitioners working in the teacher training sector. Kenan Dikilitaş is an English Language Teacher (ELT) educator and researcher working in the ELT Department of Bahçeşehir University, Turkey. Ali Bostancıoğlu is an English as a Foreign Language (EFL) tutor and researcher working in the School of Foreign Languages of Iskenderun Technical University, Turkey.